1996
DOI: 10.1093/cercor/6.2.207
|View full text |Cite
|
Sign up to set email alerts
|

Human Cingulate and Paracingulate Sulci: Pattern, Variability, Asymmetry, and Probabilistic Map

Abstract: Recent advances in functional neuroimaging of the human cerebral cortex revived interest in the study of the cortical morphology at both macro- and microscopic levels. By means of high-resolution magnetic resonance imaging (MRI), in vivo images of the human brain can be acquired and used to aid localization of the functional maps. The goal of the present study was to determine variability in the occurrence and location of the cingulate sulcus (CS) and the paracingulate sulcus (PCS). Brain MRIs of 247 healthy y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
228
1
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 325 publications
(256 citation statements)
references
References 25 publications
17
228
1
5
Order By: Relevance
“…However, the anatomy of the cingulate sulcus is highly variable between subjects (Vogt et al, 1995;Paus et al, 1996), and cellularly the borders between MPMC and CMA can be difficult to define (Russo et al, 2002;Johansen-Berg et al, 2004). The ventral limit of MPMC, as determined by our analysis, varied depending on its rostro-caudal location (Fig.…”
Section: Ventral Limit Of Mpmcmentioning
confidence: 85%
“…However, the anatomy of the cingulate sulcus is highly variable between subjects (Vogt et al, 1995;Paus et al, 1996), and cellularly the borders between MPMC and CMA can be difficult to define (Russo et al, 2002;Johansen-Berg et al, 2004). The ventral limit of MPMC, as determined by our analysis, varied depending on its rostro-caudal location (Fig.…”
Section: Ventral Limit Of Mpmcmentioning
confidence: 85%
“…The boundaries of CC were defined according to the descriptions provided in a previous study (Beckmann et al., 2009). The ventral boundaries of the region of interest (ROI) were the corpus callosum and rostral sulcus (Paus, Otaky, et al., 1996; Paus, Tomaiuolo, et al., 1996). The paracingulate sulcus (when present) was considered as the anterior and dorsal limit of the ROI.…”
Section: Methodsmentioning
confidence: 99%
“…The paracingulate sulcus (when present) was considered as the anterior and dorsal limit of the ROI. When the paracingulate sulcus was absent, the dorsal bank of the cingulate sulcus was considered as the dorsal boundary of the ROI at anterior positions and at more posterior levels (Paus, Otaky, et al., 1996; Paus, Tomaiuolo, et al., 1996). The dorsal boundary of the ROI followed a line that was imagined between neighboring portions of the cingulate sulcus, whenever the cingulate sulcus appeared break.…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the spatial distribution of subregions in normal subjects' brains have shown high interindividual variability (Amunts et al, 1999(Amunts et al, , 2000Paus et al, 1996). Additionally, interindividual variability in certain anatomical landmarks (Hunton et al, 1996;Steinmetz et al, 1989;Van Essen and Drury, 1997) has been reported to be of the order of centimeters even after Talairach transformation, which normalizes global size, position, and orientation.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, many groups have noted the importance of probabilistic atlases and have made probability maps using different modalities and different methodologies. Probability maps for subregions of normal brains have been reported (Amunts et al, 1999(Amunts et al, , 2000Kennedy et al, 1998;Leonard et al, 1998;Loftus et al, 1995;Paus et al, 1996;Penhune et al, 1996;Rademacher et al, 2001aRademacher et al, ,b, 2002Thompson et al, 1996a;Tomaiuolo et al, 1999;Varnavas and Grand, 1999;Westbury et al, 1999;White et al, 1997).…”
Section: Introductionmentioning
confidence: 99%